Optimalisasi Respons Surface Terhadap Profil Asam Tempe Lotus (Nelumbo nucifera) Rawa Perikanan - Sherly Ridhowati; Krisdayanti Nainggolan; Sabri Sudirman (Jurnal FishtecH, 2022)
This study aimed to determine the best using of combination processes in the manufacture of lotus tempeh and determine the dominant acid profile in lotus seeds tempeh. This study was conducted with 2 stages of research design, the first stage was optimization of the best process in the manufacture of fermented lotus (lotus tempeh) using the Response Surface Methodology (RSM) box Behnken with data analysis by Minitab software version 19. In the second stage, the optimal data of the first stage analyzed by descriptive analysis of acid profile and alcohol content. Based on the measurement of acid content in lotus seed tempeh ranged from 4.33-20.5% for the best combination treatments (0.5 g starter, 24 h soaking time, and 36 h fermentation time), and the alcohol content in optimal tempeh obtained from 4.74% to 5.06%. The optimal lotus tempeh has 46 compounds in acid profile as tempeh flavour, wherein cyclobutanol and ethanol as the dominant compound in the acid profile.